The Neutrophil-to-Lymphocyte Ratio Is an Important Indicator Predicting In-Hospital Death in AMI Patients - Ji, Zhenjun; Liu, Guiren; Guo, Jiaqi; Zhang, Rui; Su, Yamin; Carvalho, Abdlay; Qu, Yangyang; Zuo, Wenjie; Yao, Yuyu; Lin, Jie; Ma, Genshan (Frontiers in Cardiovascular Medicine, 2021)
Objective: To explore the role of neutrophil-to-lymphocyte ratio (NLR) in predicting the short-term prognosis of NSTEMI and STEMI. Methods: This study was a single-center, retrospective and observational study. 2618 patients including 1289 NSTMI and 1329 STEMI patients were enrolled from June 2013 to February 2018 in Zhongda Hospital, Southeast University. The demographic information, clinical characteristics, medical history, laboratory examination, treatment, and outcome of individuals at admission and during hospitalization were extracted from the electronic medical record system. Outcome was defined as the all-cause death during hospitalization. Results: (1) In the NSTEMI group, the ability of NLR in predicting in-hospital death (AUC = 0.746) was higher than the neutrophil-monocyte ratio (NMR) (AUC = 0.654), the platelet-lymphocyte ratio (PLR) (AUC = 0.603) and the lymphocyte-monocyte ratio (LMR) (AUC = 0.685), and also higher than AST (AUC = 0.621), CK (AUC = 0.595), LDH (AUC = 0.653) and TnI (AUC = 0.594). The AUC of NLR in the STEMI group was only 0.621. (2) The optimal cut-off value of NLR in NSTEMI group was 5.509 (Youden index = 0.447, sensitivity = 77.01%, specificity = 67.72%). After adjusting variables including age, sex, diabetes history, smoking history, LDL-C and Cr, the logistic regression showed that the patients with NLR>5.509 had higher hazard risk of death (HR4.356; 95%CI 2.552–7.435; P < 0.001) than the patients with NLR ≤ 5.509. (3) Stratification analysis showed that the in-hospital mortality of patients with NLR > 5.509 was 14.611-fold higher than those with NLR ≤ 5.509 in patients aged <76, much higher than the ratio in patients aged ≥ 76. For patients with creatinine levels ≤ 71, the in-hospital death risk in high NLR group was 10.065-fold higher than in low NLR group (95%CI 1.761–57.514, P = 0.009), while the HR was only 4.117 in patients with creatinine levels > 71. The HR in patients with or without diabetes were 6.586 and 3.375, respectively. The HR in smoking or no smoking patients were 6.646 and 4.145, respectively. The HR in patients with LDL-C ≥ 2.06 or <2.06 were 5.526 and 2.967 respectively. Conclusion: Compared to NMR, PLR, and LMR, NLR had the best ability in predicting in-hospital death after NSTEMI. Age, creatinine, LDL-C, diabetes and smoking history were all important factors affecting the predictive efficiency in NSTEMI. NLR had the limited predictive ability in STEMI.